2B4 engagement mediates rapid LFA-1 and actin-dependent NK cell adhesion to tumor cells as measured by single cell force spectroscopy - Hoffmann, Sabrina; Cohnen, André; Ludwig, Thomas; Watzl, Carsten (The journal of immunology, 2011)
Adhesion to tumor target cells is essential for initiation and execution of cellular cytotoxicity. In this study, we use single cell force spectroscopy to determine the exact biophysical values of the interaction forces between NK cells and tumor cells. We show that engagement of the activating NK cell receptor 2B4 can rapidly mediate an increase in the force necessary to separate NK cells from tumor cells, starting from 1 nN and increasing to 3 nN after only 120 s tumor cell contact. This early adhesion was mediated by the integrin LFA-1 and dependent on the actin cytoskeleton. The ability of NK cells to rapidly adhere to tumor target cells is consistent with their function in innate immune responses. Our data further suggest that a killing decision is already made within 120- 300 s of tumor cell contact, supporting the essential function of cell adhesion during the early phase of cellular cytotoxicity.
Gesehen am 21.07.2022